Antiaromaticity Gain Increases Potential for n-Type Charge Transport in Hydrogen-Bonded π-Conjugated Cores - Wen, Z. (Chem Commun (Camb), 2020)
Density functional theory computations suggest that formally non-aromatic organic dyes, like diketopyrrolopyrrole, naphthodipyrrolidone, indigo, and isoindigo, show increased [4n] π-antiaromatic character and decreased LUMO orbital energies upon hydrogen bonding, making them suitable molecular candidates for applications in n-type organic field effect transistors.